Optimization of Rural Residential Areas in Flood Detention Basins Based on Dual Minimum Accumulation Resistance Model: A Case Study of Xun County in Central China - Enxiang Cai; Shihong Long; Ling Li; Ying Luo; Liling Ge; Weiqiang Chen; Guoquan Li (Land)
Optimizing rural residential areas (RRAs) in environmentally fragile areas such as flood detention basins is of great significance for improving the human–land relationship and achieving sustainable rural development. This study took Xun County in central China as a case study, established a dual minimum cumulative resistance model (DMCR) that considered the dual factors of natural attributes and policy regulations to evaluate the optimization resistance of RRAs and determined the optimization directions and strategies accordingly. The main results are: (1) RRAs are relatively small and scattered, and there are spatial conflicts with policy regulations such as flood detention basin and urban development boundaries. (2) The spatial difference in optimization resistance of RRAS is higher in the central and northern towns and lower in the western and eastern towns. The factors with significant effects include policy resistance, location resistance, and production resistance. (3) The optimization of RRAs is divided into three directions: annexation or evacuation, consolidation and improvement, and clustering and upgrading, with their respective area proportions of 31.17%, 48.12%, and 20.72%. (4) RRAs in the direction of clustering and upgrading allow for moderate expansion; RRAs in the direction of consolidation and improvement achieve smart reduction through the renovation of homesteads; RRAs in the direction of annexation or evacuation are gradually integrated into the urban area in the suburbs and completely demolished in the outer suburbs.